2018
DOI: 10.1111/eva.12706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic decline, restoration and rescue of an isolated ungulate population

Abstract: Isolation of small populations is expected to reduce fitness through inbreeding and loss of genetic variation, impeding population growth and compromising population persistence. Species with long generation time are the least likely to be rescued by evolution alone. Management interventions that maintain or restore genetic variation to assure population viability are consequently of significant importance. We investigated, over 27 years, the genetic and demographic consequences of a demographic bottleneck fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Potential concerns about outbreeding depression and/or genomic swamping of the AENP buffalo population following this proposed genetic supplementation could be alleviated by considering the current support for an estimated short time since isolation (~100 years) [ 17 , 49 ] and by conducting regular genetic monitoring of the population. Furthermore, recent studies showed local genes, and alleles related to local adaptation, were maintained in the recipient population after genetic supplementation, while the benefits of genetic rescue were still observed [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential concerns about outbreeding depression and/or genomic swamping of the AENP buffalo population following this proposed genetic supplementation could be alleviated by considering the current support for an estimated short time since isolation (~100 years) [ 17 , 49 ] and by conducting regular genetic monitoring of the population. Furthermore, recent studies showed local genes, and alleles related to local adaptation, were maintained in the recipient population after genetic supplementation, while the benefits of genetic rescue were still observed [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although expected heterozygosity may be slower at responding to recent demographic setbacks than allelic richness, it is less sensitive to difference in sample size. Moreover, recent longitudinal studies have shown that H E is sensitive to anthropogenic disturbance, and that significant reductions in expected heterozygosity can be observed several generations after a population bottleneck 109 , 110 . For example, a South-African lion population suffered a 10–13% reduction in expected heterozygosity as compared to museum samples collected 100 years earlier (ca.…”
Section: Methodsmentioning
confidence: 99%
“…To test for spatial autocorrelation, we used an autocorrelogram approach assessing the relationship between Moran’s I of model residuals and pairwise geographical distance 109 . We did not find evidence for patterns of spatial autocorrelation neither for the animal kingdom model nor for the plant kingdom model (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Numbers declined rapidly in 1997–2001, partly because of cougar ( Puma concolor ) predation (Festa‐Bianchet et al, ), then stagnated at about 40 for several years. Thirty‐two sheep were transplanted to Ram Mountain between 2003 and 2015, from a population about 130 km to the north–west (Poirier, Coltman, Pelletier, Jorgenson, & Festa‐Bianchet, ). Trophy hunting ended in 2010 (Pigeon, Festa‐Bianchet, Coltman, & Pelletier, ); 64 males were shot between 1972 and 2007.…”
Section: The Field Studiesmentioning
confidence: 99%